Evolution of Collagenous Colitis into Severe and Extensive Ulcerative Colitis - Hugh J Freeman; Ken W Berean; Michael Nimmo (Canadian Journal of Gastroenterology)
Collagenous colitis is an inflammatory mucosal disorder of the colon with distinctive histopathological features, including a thickened subepithelial collagen layer. The clinical course is usually benign, but serious complications, including death, may occur. In the present report, a 69-year-old woman with watery diarrhea and collagenous colitis developed bloody diarrhea that was refractory to treatment medications, including corticosteroids and azathioprine. Endoscopic and histopathological studies showed a focal neutrophilic inflammatory process that progressed to a diffuse and extensive form of colitis, eventually requiring total proctocolectomy. Careful histological review of the resected colon showed no evidence of persistent collagenous colitis. These findings suggest an important need for continued long-term follow-up of patients with collagenous colitis because superimposed and serious colonic complications may occur, including a severe and extensive pancolitis refractory to medications and necessitating total proctocolectomy.